Effect of Sleep Deprivation on Simulated Microsurgical Vascular Anastomosis - Ito, Yoshiro; Hafez, Ahmad; Hosoo, Hisayuki; Marushima, Aiki; Matsumaru, Yuji; Ishikawa, Eiichi (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2023)
Background The effects of sleep deprivation on surgical performance have been well documented. However, reports on the effects of sleep deprivation on microneurosurgery are limited. This study aimed to investigate the effects of sleep deprivation on microneurosurgery.Methods Ten neurosurgeons participated in the anastomosis of a vessel model using a microscope in sleep-deprived and normal states. We evaluated the procedure time (PT), stitch time (ST), interval time (IT), number of unachieved movements (NUM), leak rate, and practical scale for anastomosis quality assessment. Each parameter was compared between normal and sleep-deprived states. Subanalyses were performed on the two groups based on PT and NUM under the normal state (proficient and nonproficient groups).Results Although no significant differences were noted in PT, ST, NUM, leak rate, or practical scale, IT was significantly prolonged under sleep deprivation compared with the normal state (mean: 258.8 ± 94.0 vs. 199.3 ± 74.9 seconds; p = 0.02). IT was significantly prolonged under sleep deprivation in the nonproficient group based on both PT and NUM (PT: 234.2 ± 71.6 vs. 321.2 ± 44.7 seconds, p = 0.04; NUM: 173.3 ± 73.6 vs. 218.7 ± 97.7; p = 0.02), whereas no significant difference was observed in the proficient group (PT: 147.0 ± 47.0 vs. 165.3 ± 61.1 seconds, p = 0.25; NUM: 173.3 ± 73.6 vs. 218.7 ± 97.7; p = 0.25).Conclusions Although IT was significantly prolonged under sleep deprivation in the nonproficient group, there was no decline in performance skills in either the proficient or nonproficient group. The effect of sleep deprivation may require caution in the nonproficient group, but it is possible that certain microneurosurgical outcomes can be achieved under sleep deprivation.
Keywords: sleep deprivation; microsurgical vascular anastomosis; nonproficient; individual level; work-hour restrictions